Iron-Photocatalyzed Decarboxylative Oxygenation of Aliphatic Carboxylic Acids - Denkler, Luca Mareen; Shekar, Meghana Aladahalli; Bunescu, Ala (Synlett, 2025)
Carboxylic acids, a bench-stable, readily available, and structurally diverse class of compounds, represent ideal starting materials for organic synthesis. In this article, we highlight an iron-catalyzed, decarboxylative, C(sp3)–O bond-forming reaction that takes place under mild, photocatalytic, base-free conditions using 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) derivatives as oxygenation reagents. The reaction is enabled by the ability of iron complexes to generate carbon-centered radicals directly from carboxylic acids through a sequence involving a photoinduced carboxylate-to-iron charge transfer, homolysis, and loss of carbon dioxide. The developed transformation displays exquisite substrate tolerance and was applied to various bioactive molecules. We performed an extensive mechanistic investigation through kinetic studies; electrochemistry, EPR, UV/Vis, and HRMS analyses; and DFT calculations. Those studies suggest that TEMPO plays three different roles in the reaction: it acts as an oxygenation reagent, serves as an oxidant to regenerate the Fe catalyst, and functions as an internal base for carboxylic acid deprotonation. The resulting TEMPO adducts are versatile synthons that can be subsequently utilized in C–C and C–heteroatom bond-forming reactions employing commercially available organophotocatalysts and nucleophilic reagents.1 Introduction2 Background on the LMCT Reactivity of Iron Complexes3 Direct Iron-Photocatalyzed Decarboxylative Oxygenation: Reaction Concept4 Substrate Scope Assessment of Decarboxylative Oxygenation5 Mechanistic Considerations6 Conclusion
Keywords: decarboxylation; oxygenation; photocatalysis; carboxylic acids; iron catalysis; TEMPO